Characterization of Five Escherichia coli Isolates Co-expressing ESBL and MCR-1 Resistance Mechanisms From Different Origins in China - Zhang, Pei; Wang, Juan; Wang, Xinglong; Bai, Xue; Ma, Jiangang; Dang, Ruyi; Xiong, Yifei; Fanning, Séamus; Bai, Li; Yang, Zengqi (Frontiers in Microbiology, 2019)
In this study, we characterized five co-expressing ESBL and MCR-1 Escherichia coli recovered from food, food-producing animals and companion animals in China. Antimicrobial susceptibility tests, conjugation experiments, and plasmid typing were performed. Whole genome sequencing (WGS) was also undertaken for all five isolates using either PacBio RS II or Illumina HiSeq 2500 platforms. The cefotaxime and colistin resistance encoded by blaCTX-M and mcr-1 genes respectively was transferable by conjugation either together or separately for all five strains. Interestingly, the ESBL and mcr-1 genes could be co-selected by cefotaxime, while the colistin only selected the mcr-1-carrying plasmids during the conjugation experiments. Five E. coli sequence types were detected: ST88, ST93, ST602, ST162, and ST457. Although diverse plasmid profiles were identified, IncI2, IncFIB and IncFII plasmid types were predominant. These five clonally unrelated isolates harbored the mcr-1 gene located on similar plasmid backbones, which showed high nucleotide similarity to plasmid pHNSHP45. The mcr-1 gene can be disseminated via multiple mobile elements (with or without ISApl1) and be co-transmitted with blaCTX-M genes through IncI2 plasmids. Characterization of these co-existence ESBL and mcr-1 isolates extends our understanding on the dissemination of these resistance markers among bacteria of diverse origins.